Digital human modelling over four decades. (2016) - Case, Keith; Marshall, Russell; Summerskill, Steve
This paper aims to provide a retrospective of the use of a digital human modelling tool (SAMMIE) that was perhaps the first usable tool and is still active today. Relationships between digital human modelling and inclusive design, engineering design and ergonomics practice are discussed using examples from design studies using SAMMIE and government-funded research. Important issues such as accuracy of representation and handling multivariate rather than univariate evaluations are discussed together with methods of use in terms of defining end product users and tasks. Consideration is given to the use of the digital human modelling approach by non-ergonomists particularly with respect to understanding of the impact of human variability, jurisdiction and communication issues.